2014
DOI: 10.3341/kjo.2014.28.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Current Practice Pattern for Dry Eye Patients in South Korea: A Multicenter Study

Abstract: Purpose: To assess current practice patterns for dry eye patients in South Korea and to evaluate the preference according to the ages and clinic types of physicians. Methods: Dry eye patients (n = 1,612) were enrolled in this multicenter cross-sectional, observational study. The severity level of dry eye patients was classified based on the Korean guidelines for dry eye treatment. The medical records of the enrolled dry eye patients were evaluated, and the practice styles and the preferences were analyzed acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Although this study did not differentiate between level 1 and 2 severity, the proportion of dry eye severity in this study was similar to that published by Song et al 21 In South Korea, where dry eye severity was based on a classification modified from the DEWS guideline, the prevalence of patients with dry eye at level 1 was 47.5%, 33.5% at 2 (ie, 81.0% if levels 1 and 2 were combined), 9.1% at level 3, and 1.1% at level 4. These numbers closely related to our findings of 88.2% at level 1 or 2, 9.0% at level 3, and 2.6% at level 4.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although this study did not differentiate between level 1 and 2 severity, the proportion of dry eye severity in this study was similar to that published by Song et al 21 In South Korea, where dry eye severity was based on a classification modified from the DEWS guideline, the prevalence of patients with dry eye at level 1 was 47.5%, 33.5% at 2 (ie, 81.0% if levels 1 and 2 were combined), 9.1% at level 3, and 1.1% at level 4. These numbers closely related to our findings of 88.2% at level 1 or 2, 9.0% at level 3, and 2.6% at level 4.…”
Section: Discussionsupporting
confidence: 90%
“…It is scored on a scale of 0 to 100, with higher scores representing greater disability. Based on the OSDI score, the ocular surface was defined as normal (0-12), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23-32), or severe (33-100). 19 Clinicians were masked to patients' OSDI scores.…”
Section: Severity Of Dedmentioning
confidence: 99%
“…There is some evidence to suggest that CsA is accepted and frequently prescribed by eye care providers for the treatment of DED. 50 The American Academy of Ophthalmology Preferred Practice Pattern 11 includes CsA in the discussion on dry eye management. Furthermore, a retrospective study of dry eye medication use and expenditures in the US showed an increase in dry eye medication prescriptions from 2001 to 2006 that was largely driven by CsA.…”
Section: Patient Perspective On the Use Of Topical Cyclosporine 005%mentioning
confidence: 99%
“…Dry eye (DE) syndrome is one of the most frequent diseases encountered by ophthalmologists, and has a prevalence of 30% to 50% in the entire population [ 1 2 3 ] and a significant impact on daily life [ 4 5 6 ]. The etiology of DE syndrome has not been clearly established despite significant research efforts; however, according to previous studies, DE is likely an immunological disorder [ 7 ].…”
mentioning
confidence: 99%